Raiz dentária impelida para o seio maxilar após exodontia: uma opção de tratamento - Ponzoni, Daniela [UNESP]; Aranega, Alessandra Marcondes [UNESP]; Faverani, Leonardo Perez [UNESP]; Ferreira, Gabriel Ramalho [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP]; Bassi, Ana Paula Farnezi [UNESP] (My University, 2011)
Introduction: Upper teeth, especially first premolars and molars, can have a close anatomical relationship with the floor of maxillary sinus. For this reason, accidental displacement of dental roots into the sinus could happen during exodontic procedures. Objective: Description the treatment performed to remove a tooth root within the maxillary sinus, displaced during an extraction procedure. Case Report: Female patient, 39 years of age, which reported being subjected to the extraction of the element 26 for about two months. The patient was reported by the practitioner who performed the extraction that a root was pushed into the maxillary sinus. The treatment plan included surgery to remove the root within the maxillary sinus. Final Comments: Clinicians should be careful during extractions, to prevent these accidents. However, if such complications occur, access to the maxillary sinus is the best treatment option.

Introdução: A íntima relação anatômica entre raízes dentárias e o assoalho do seio maxilar, principalmente na região de pré-molares e primeiro molar superiores, podem levar ao deslocamento acidental de raízes para o interior do seio maxilar nos procedimentos de exodontia. Objetivo: Descrição do tratamento realizado para a remoção de uma raiz dentária no interior do seio maxilar, deslocada durante um procedimento de exodontia. Relato de Caso: Paciente do sexo feminino, 39 anos de idade, que relatou ter sido submetida à extração do elemento 26 para cerca de dois meses. O paciente foi informado pelo profissional que realizou a extração de uma raiz que foi impelido para o interior do seio maxilar. O plano de tratamento incluiu a cirurgia para remover a raiz no seio maxilar. Comentários Finais: Os profissionais devem ser criteriosos durante as extrações dentárias, para evitar estes acidentes. Entretanto, caso ocorra esta intercorrência, o acesso ao seio maxilar é a melhor opção terapêutica.
Dental root displaced to maxillary sinus after tooth extraction: a treatment option
Keywords: Accidents; Maxillary sinus; Tooth root; Acidentes; Seio maxilar; Raiz dentária